Determination and correlation of the solubility of myricetin in ethanol and water mixtures from 288.15 to 323.15K. (2nd January 2017) - Cai, Shaona; Zhang, Peipei; Zhou, Li; Jing, Ting; Fan, Huihui; Lin, Rong; Yang, Guangde; Wang, Weirong; Zhang, Jiye
ABSTRACT: The solubility of myricetin (MY) is very important in regard to its extraction and purification, which was performed by an equilibrium method in the binary solvent system of ethanol and water in the temperature range 288.15 323.15 K and was determined by ultraviolet (UV-Vis) spectrophotometry at 375 nm. The experimental solubility values were correlated by four mathematical equations: a simplified universal equation (ideal model), modified Apelblat equation, equation and Jouyban–Acree equation. The modified Apelblat model is more suitable for predicting the solubility data of MY in the binary solvent system of ethanol and water at this experimental temperature range. The dissolution enthalpy and entropy of MY were evaluated by the Van't Hoff and Gibbs−Helmholtz equations. The results illustrate that the dissolution process in binary system solvent mixtures is strongly dependent on solvent composition and temperature, and this process was endothermic and entropy driven. GRAPHICAL ABSTRACT: